Penguatan Kewirausahaan Berbasis Digital pada Mahasiswa Tingkat Akhir di PSDKU UNTAD Morowali - Mohammad Ega Nugraha; Armawati; Jusriadi; Asbal Rasyid (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
The target of this service is to build a business in the digitalization era aimed at final year students consisting of three study programs namely Agrotechnology, Management Studies and Civil Engineering) at PSDKU UNTAD Morowali. The purpose of this service is how to provide a broader understanding to final year students of PSDKU UNTAD Morowali to improve entrepreneurial competence after completing education in college and the purpose of this socialization is to anticipate students after finishing college so that they are not unemployed, so that they fill time and even become jobs that cultivated to be able to open a business online through applications on social media. The implementation method in the community service program is to provide material/lectures on strengthening entrepreneurship material in the digitalization era in the form of digital applications that are used to build further business in the current digital era. The final result of community service is expected to be useful for final year students of PSDKU UNTAD  Morowali to strengthen the entrepreneurial spirit and take advantage of the use of social media to open a business and start a business.